2015
DOI: 10.3167/latiss.2015.080304
|View full text |Cite
|
Sign up to set email alerts
|

An emotional journey of identity change and transformation: The impact of study-abroad experience on the lives and careers of Chinese students and returnees

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk An emotional journey of identity change and transformationThe impact of study-abroad experience on the lives and careers of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Simultaneously, YP 1 is dealing with the challenges of adjustment, change, particularly relocating from a generally homogeneous to a heterogeneous environment, a sense of not belonging and alienation. Studies report these experiences and transitions by international students are not uncommon (Gu, 2015;Wu, Garza, & Guzman, 2015). Nonetheless, the responses show the YPs are confident about how they perceive themselves and their cultural identity, which appears to be strong.…”
Section: Identitymentioning
confidence: 92%
See 2 more Smart Citations
“…Simultaneously, YP 1 is dealing with the challenges of adjustment, change, particularly relocating from a generally homogeneous to a heterogeneous environment, a sense of not belonging and alienation. Studies report these experiences and transitions by international students are not uncommon (Gu, 2015;Wu, Garza, & Guzman, 2015). Nonetheless, the responses show the YPs are confident about how they perceive themselves and their cultural identity, which appears to be strong.…”
Section: Identitymentioning
confidence: 92%
“…Identity constantly involves negotiation and transformation as each individual negotiates their economic, political and cultural dependency in different ways (Hall, 1994). Gu's (2015) research on Chinese study abroad students and returnees affirms their learning experiences necessitate identity change which occurs across different settings and through different processes such as socialization and acculturation. She suggests that the crux of identity change is the emotional sense of belonging whether it be as an individual, a member of a professional group or an organization.…”
Section: Communities Of Practice and Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This act illustrates how the Chinese government uses non-governmental tools in public policy and concentrates on spreading the Chinese culture through academic knowledge exchange. Gu demonstrated that Chinese overseas students become both more firmly committed to Chinese culture and more understanding to the host country's culture during the time in abroad [27].…”
Section: Overview On the State Policy Perceptionsmentioning
confidence: 99%
“…This questioning of the familiar can also be sharpened in political discussions, where Chinese students are held accountable for CCP policies and where the negotiation of intercultural identities is consequently not necessarily a harmonious process (Hansen and Thøgersen 2015). Gu (2015) has demonstrated how Chinese international students actually become both more firmly committed to their own culture and more understanding towards the host culture during their time abroad. However, as the quote from the Chinese international student at Aalborg University at the beginning of this section illustrates, sometimes the interaction actually leads to defensiveness and entrenchment rather than a greater intercultural understanding.…”
Section: Returning -Changed Attitudes and Values?mentioning
confidence: 99%